Estimation of Synchrophasor Parameters in the Presence of 3rd & 5th Harmonics and White Gaussian Noise - Gizaw, Kassaye; Ygzaw, Alganesh; Bantyirga, Belachew; Aberie, Habtemariam (Advances of Science and Technology, 2021)
Nowadays, power systems, particularly distribution networks, often operate close to their stability limit due to the rapid growth of new customers and inauguration of industrial sectors. Though the advancement of renewable energy sources (RESs) and Flexible Alternating Current Transmission (FACT) devices are the right solutions to meet these demands, they increase the network’s complexity and dynamic behavior. To solve these complexities, introducing advanced controllers that are fast, accurate, and have a reliable synchronization method is the most effective solution. On this basis, one of the foremost promising technologies that constitute the backbone of wide-area and local monitoring systems in real-time is the Phasor Measurement Units (PMU) device. Thus, in this paper, the synchrophasor estimation (SE) algorithm, which is the main component to build up a PMU, is developed using the iterative interpolated DFT technique. Even if the analyzed interferences are two harmonics (3rd and 5th), the developed algorithm can work for any type and number of interferences. Based on the simulation result demonstration, the algorithm can effectively estimate the amplitude, phase, and frequency within the maximum error of 0.039, 0.002, and 0.0001. This research work can solve various interrelated problems of electrical utilities for those lacking a tool that can trace the system at proper time snapshot like in our country Ethiopia.